2019
DOI: 10.1039/c9ra08630g
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilically activated nitroalkanes in reaction with aliphatic diamines en route to imidazolines

Abstract: Imidazolines were assembled via an unusual reaction between nitroalkanes and aliphatic 1,2-diamines in the presence of phosphorous acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel-Crafts-type C-H functionalization reactions, often with subsequent accompanying rearrangements [21][22][23][24]. Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel-Crafts-type C-H functionalization reactions, often with subsequent accompanying rearrangements [21][22][23][24]. Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well.…”
Section: Resultsmentioning
confidence: 99%
“…Next, a mixture of 86% orthophosphoric acid and 87% polyphosphoric acids (approximately corresponding to anhydrous H 3 PO 4 ) or molten 87% polyphosphoric acid (PPA) were employed as the media for the reactions carried out at 120 • C. Again, the reactions did not proceed, and the starting amine 1a remained intact in both cases (entries 3, 4). As it was shown in our previous report [25] that addition of phosphorous acid to the reaction medium could enable stubborn steric-restricted annulations, we also decided to attempt to stimulate the reactivity using this trick. To this end, the reaction of 1a and 4c was carried out in a mixture of H 3 PO 3 and 87% PPA (1:1 m/m) at 130 • C. Formation of product 3ac was detected, albeit in a low yield (entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…It was also discovered that the nucleophilic amines 3 can be successfully employed in this type of transformations as well, providing the amidinium intermediates 4 , which are susceptible to a variety of subsequent cyclizations. This approach opens up a novel avenue by which to access the benzoxazoles 5 [ 40 ], benzimidazoles 6 [ 40 41 ], diazines 7 [ 42 43 ], or imidazolines 8 ( Scheme 1 ) [ 44 ]. We have also shown that a nucleophilic attack on the phosphorylated nitronate species 2 can be carried out with the participation of N -acylhydrazides or thiosemicarbazides to afford the 1,3,4-oxadiazoles 9 [ 45 ] and the 1,3,4-thiadiazoles 10 [ 46 ], respectively ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative, more appealing method would capitalize on the in situ generation of a less sterically hindered, and therefore more reactive electrophilic nitronate. As we have recently demonstrated, this type of species can be efficiently generated upon the treatment of nitroalkanes with anhydrous H 3 PO 4 or in combination with 87% PPA [ 44 ]. We were pleased to find that the performance of the direct transformation of 12 into 16a was significantly improved after doping the PPA medium with H 3 PO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation